ANALISIS PEMBELAJARAN MATEMATIKA DENGAN MENGGUNAKAN PENDEKATAN KONTEKSTUAL MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) - Helmi Nurlela; Anik Yuliani; Luvy Sylviana Zanthy (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to determine the implementation and students response of mathematics learning through a contextual approach with a Number Head Together (NHT) type of learning model.this study use descriptive methods, namely research that can be understood at a research procedure that utilizies descriptive data. The subjects of this study were students of class VII A SMP PGRI Leuwi Gajah for the 2019/2020 academic year even semester. The instruments used questionnaires for student responses. The results showed that learning with the contextual approach of the NHT model was running according to the lesson plans that had been provided and for students responses showing positive results. Students become more active in participating learning so that learning becomes more fun.